2019
DOI: 10.1038/s41598-019-47063-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Changes in Conformation of Calmodulin with Calcium Binding and/or Target Recognition

Abstract: Calmodulin is a calcium binding protein with two lobes, N-lobe and C-lobe, which evolved from duplication and fusion of a single precursor lobe of a pair of EF-hand. These two lobes of calmodulin show subtle differences in calcium binding and target recognition; these are important for the functions of calmodulin. Since the structures, especially main chain conformations, of two EF-lobes in holo-form are quite similar; this is a good example to evaluate the effect of side chains for structural dynamics. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…Multivalent ions can cause changes in the sizes of the polyelectrolyte chains and alter their local conformations. It has been shown that Ca 2+ ions can induce specific secondary structures in different peptides not only by screening electrostatics but also by forming ion bridges between anionic monomers [39][40][41]. We have performed atomistic MD simulations to investigate the effects of CaCl2 salt on conformations of PASA and PGA.…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent ions can cause changes in the sizes of the polyelectrolyte chains and alter their local conformations. It has been shown that Ca 2+ ions can induce specific secondary structures in different peptides not only by screening electrostatics but also by forming ion bridges between anionic monomers [39][40][41]. We have performed atomistic MD simulations to investigate the effects of CaCl2 salt on conformations of PASA and PGA.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these globular clusters can bind up to two free Ca 2+ ions via a pair of helix-loop-helix motives (EF-hands) in a cooperative manner (K d = 5 · 10 −7 M to 5 · 10 −6 M) [ 16 , 17 , 18 ]. Because of subtle structural differences between these lobes resulting from evolutionary processes [ 19 ], EF hands in the C-lobe exhibit a three- to five times higher affinity for Ca 2+ . However, they possess slower rate of ion binding than the regions of EF hands located in the N-lobe, establishing the broad range of CaM sensitivity to the changes in calcium concentrations in the intracellular space [ 20 ].…”
Section: Calmodulin—ubiquitous Ca 2+ Sensor In mentioning
confidence: 99%
“…In order to overcome the limitations imposed by analyzing static crystal structures, we have employed molecular dynamics (MD) simulations to probe the RyR2–CaM binding interface at the level of individual amino acid residues. Aside from the RyR2–CaM system, several previous studies have used MD simulations to explore the dynamics and binding interactions of CaM and other CaM-like proteins with various peptide targets. As an important test case, we have modeled our computational study after an experiment carried out by Nakamura et al…”
Section: Introductionmentioning
confidence: 99%